Assessing the effectiveness of a narrative-based patient education video for promoting opioid tapering. Issue 2 (February 2021) - Feng, Bo; Malloch, Yining Z.; Kravitz, Richard L.; Verba, Susan; Iosif, Ana-Maria; Slavik, George; Henry, Stephen G.
Highlights: Five thousand participants were screened to identify eligible US patients. Patients randomized to view a narrative video or pamphlet about opioid tapering. Perceived tapering effectiveness was higher in the video than the pamphlet group. Perceived self-efficacy was higher in the video than the pamphlet group. Post-intervention tapering intention did not differ between groups. Abstract: Objective: To compare effectiveness of a narrative-based educational video versus an informational pamphlet for increasing patients' self-efficacy and intention to taper their opioid use. Methods: Five thousand participants recruited from MTurk were screened to identify eligible patients. Eligible participants ( n = 365, 49.9 % female, mean age = 37 years) were randomized to either watch the narrative video or read the pamphlet. Linear regression models were used for the main analysis. Results: Participants' perceptions of tapering effectiveness were higher in the video group (mean = 4.06) than the pamphlet group (mean = 3.67), adjusted mean difference = 0.34, 95 %CI 0.13 - 0.54, P < 0.001. Participants' perceptions of tapering self-efficacy were also higher in the video group (mean = 3.97) than the pamphlet group (mean = 3.60), adjusted mean difference = 0.32, 95 %CI 0.09 – 0.55, P < 0.001. Perceived tapering effectiveness and self-efficacy were both positively associated with post-intervention tapering intention (Spearman rank correlation coefficient = 0.38 and 0.53, respectively, both P < 0.001). Conclusion: A narrative-based video about opioid tapering enhanced patients' perceptions of the effectiveness of tapering and their tapering self-efficacy. Practice implications: Narrative-based videos may be effective for changing patient attitudes about opioid tapering.